Climate change and sustainable urban development in Africa and Asia - Yuen, Belinda K. P.; Kumssa, Asfaw (Springer, 2011)
This book is about African and Asian cities. Illustrated through selected case cities, the book brings together a rich collection of papers by leading scholars and practitioners in Africa and Asia to offer empirical analysis and up-to-date discussions and assessments of the urban challenges and solutions for their cities. A number of key topics concerning housing, sustainable urban development and climate change in Africa and Asia are explored along with how policy interventions and partnerships deliver specific forms of urban development. Audience: This book is intended for all who are interested in the state of the cities and urban development in Africa and Asia. Africa and Asia present, in many ways, useful lessons in dealing with the burgeoning urban population, and the problems surrounding this influx of people and climate change in the developing world.